A polar coordinate based sliding mode design for vibration control - Young, K. David (Zielona Góra: Uniwersytet Zielonogórski)
A polar coordinate based sliding mode control design approach for solving vibration control problems is proposed. The phase plane in subdivided into multiple sets, and a different sliding manifold can be chosen for each of the sets. This flexibility in the design allows a different variable structure control law to be applied depending on the phase angle of the vibration. Transient performance improvements over conventional VSC with sliding hyperplanes are demonstrated.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka